Getting to Know Patients - Eden, Caroline (The Hastings Center report, 2016)
As a third-year medical student, I have the job of being the first person from the medical team to check in on patients in the morning, follow up on consults that they may need, and communicate with people from other services who are involved with patients’ care. Because third-year medical students have the most time of anyone on the medical team, we are encouraged to get to know our patients. We are encouraged to take time to understand our patients’ conditions on both a medical and personal level, that is, both to read about their complex diseases and to talk about their preferences, goals, families, and lives outside the hospital. As best we can, we then communicate their personal needs and preferences to the medical team of doctors, nurses, social workers and others. What could be wrong with that?